Content validity of an analytical rubric of the design of didactic sequences as an improvement of the pedagogical practice of the teaching team from the socioformation approach - Guevara-Rodríguez, Guillermina; Veytia-Bucheli, María Guadalupe (Revista Electrónica Educare, 2021)
The educational context traditionally determines an administrative practice of planning and evaluation processes, in this sense, there is a lack of instruments to evaluate the design of didactic sequences with the challenge of granting knowledge that confront contextual problems; and make a teaching intervention with methodological bases for solving problems. The purpose of this study is to describe the design of a didactic sequence rubric for the improvement of pedagogical practice. The methodology was carried out through an instrumental study of content validity based on the socioformative approach with the following steps: 1) analysis of instruments at ends; 2) construction of a rubric with the focus of socioformation, 3) revision and improvement of the instrument by experts; 4) application of the instrument to a pilot group; and 5) validation of content by a group of judges in the educational area. The results with respect to the V of Aiken with a significance of p